ON THE CHOICE ADDRESS FORMS: INTIMATE ADDRESS FORMS AS IN-GROUP IDENTITY MARKERS OF BLACK SOUTH AFRICANS IN INVICTUS MOVIE - Prihantoro Prihantoro (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
Invictus is a movie which is adapted from a true story of how the South African President, Nelson Mandela, tried to unite South Africa by supporting the national rugby team, Springbok, which used to be the symbol of Apartheid. His relation with other characters in this movie is reflected from the address forms and the choice is influenced by many aspects like social distance among the participants, age difference, formality scale etc. This paper focuses on the choice of address forms used among the participants. Besides the variety and progressive use of address forms, the finding also shows that the choice of address forms used by âblackâ and âwhiteâ South Africans are quite different, especially those addressed to Mandela. I observed that some in-group identity markers among the blacks are realized by intimate address forms like Mandelaâs nickname Madiba, or companion address Comrade. In the past, these address forms are known as the devices to struggle against the Apartheid system.